Remission of long-standing livedoid vasculopathy using a whole foods plant-based diet with symptoms recurrent on re-challenge with standard Western diet - Smith, Morgen (BMJ Case Rep, 2021)
A 63-year-old woman presented with ulcerations of both lower legs. Symptom onset was 2006. In 2013 she saw a dermatologist and a biopsy suggested livedoid vasculopathy. In 2016 a whole food plant-based diet (WFPB) was advised as a potential treatment in the community setting. The patient changed her diet accordingly, but was not otherwise treated. The symptoms remitted completely with close adherence to the WFPB diet and recurred on multiple occasions associated with poor dietary adherence. There was a self-identified dose–response relationship with degree of adherence and number and intensity of flares. There were no known adverse side effects from the diet change, although the patient felt adherence to be difficult at times. The mechanism is not completely clear; we speculate that the dietary changes directly affect vascular endothelial health, which in turn affects propensity towards a prothrombotic state. More research is needed to elucidate potential mechanisms.